The cross-border labour market: A priority in the Eurodistrict PAMINA - Patrice Harster; Frédéric Siebenhaar (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
The paper focuses on the activities of the Eurodistrict PAMINA in the cross-border labour market, including the associated training measures. Here the concrete needs and practice-oriented approaches of a dynamic labour market region meet the complex challenges of a multi-level system, the governance of which is not fully developed. This is a constellation that has obstructed the implementation of a number of promising ideas. The Eurodistrict PAMINA lies at the interface between national and cross-border metropolitan regions and within the area of the greatest commuter flows in Europe (Upper Rhine and Greater Region), where PAMINA is testing a local strategy based primarily on bringing together the qualified actors and improving coherence between measures and funding policies.
urn:nbn:de:0156-40971706; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Cross-border labour market; joint action plan; multi-level governance system; governance; INTERREG Upper Rhine; Eurodistrict PAMINA